The lexemes functioning for denotation of the streets (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The features of lexemes functioning for denotation of street which are included in the system of names of administrative-territorial units within settlements are considered in the article.  The semantics of lexeme, its stylistic use is traced.
Keywords: lexical-semantic group; administrative-territorial lexis; semantic structure; address function